Network analysis of offensive dynamics in a Portuguese First Division football team: insights from the 2020-2021 season - Ricardo Jorge da Conceição Alves; Gonçalo Dias; Vasco Vaz; Sérgio Querido; Nuno André Nunes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Network analysis has gained increasing attention, as it provides a framework for identifying both collective and individual behaviours within the football teams.